A brief discussion and analysis of the factors that can influence students' mathematical learning (Research, Society and Development, 2022)
The present work proposes to present a research on the factors that can influence the learning of Mathematics. This situation has been the subject of debates between teachers, parents and school management, who also link this situation to the students' lack of interest. According to these teachers, this situation occurs in all subjects and is even more worrying when it comes to the Mathematics curricular component. A qualitative-quantitative research was carried out, applying data collection techniques in an elementary school in the city of Aquiraz - CE, through bibliographic sources, informal dialogues with teachers and application of a structured questionnaire for students. With the research, we realized that there are several factors that interfere in learning, such as the reality of the community, family, perspective of life and among others, being necessary to develop mechanisms that can improve the student's self-confidence and strengthen the student's relationship with the teacher.